Contemporary issue: health and safety of female wrestlers - Jagim, A. R.; Moschelli, J. S.; Woodroffe, L. M.; Horswill, C. A.; Bloomfield, S. A.; Oppliger, R. A. (Current Sports Medicine Reports, 2024)
Female wrestling has grown exponentially over the past decade. Within the United States, 46 states now recognize female high school wrestling, and 153 colleges have programs. It is on track to become an NCAA championship-level sport in 2026. A primary health and safety risk among this cohort pertains to rapid weight loss strategies. These can lead to intentional caloric restriction and decreased body fatness, with the perceived goal of attaining a competitive advantage. Low energy availability and low body fatness are associated with a number of health concerns including menstrual dysfunction and loss of bone mineral density in girls and women. The current recommendation of 12% as a minimum for percentage body fat is very likely too low, opening the door for health perturbations among this population. The minimum threshold might more appropriately fall within the range of 18% to 20%. Body fat assessment methods, primarily skinfold measures that are used to guide weight class selection, have not been adequately validated among this population and therefore should be an area of research focus, while also exploring alternative assessment techniques. Further, we recommend that weight cycling, restrictive energy intake, and intentional dehydration be avoided. Research should assess the effects of frequent weight cycling (to "make weight") and prolonged periods of low body fat on the reproductive and bone health of these athletes. Finally, research and clinical evaluations on female wrestlers are limited, and we offer a list of research priorities for future investigation into this contemporary issue.